Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd011731
|View full text |Cite|
|
Sign up to set email alerts
|

Perioperative warming therapy for preventing surgical site infection in adults undergoing surgery

Abstract: Perioperative warming therapy for preventing surgical site infection in adults undergoing surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Passive and active warming methods are used in the operating room (OR) to prevent the incidence of PH. Blanket use to provide insulation and radiant heat loss prevention (passive method), warming intravenous fluids, and patient warming devices (active methods) are well known ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive and active warming methods are used in the operating room (OR) to prevent the incidence of PH. Blanket use to provide insulation and radiant heat loss prevention (passive method), warming intravenous fluids, and patient warming devices (active methods) are well known ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a plethora of patient warming devices are utilized to reduce the incidence of intraoperative hypothermia among surgical patients ( 2 , 3 ) (Table 1 ). We focus our review on two most commonly used and widely studied methods—forced air warming (FAW) and resistive heating (RH)—based on recent publications associated with their use ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, forced warming device and device using conduction are currently mainly used as patient warming devices. 4 Although these warming devices are known to be effective in preventing hypothermia, they had to be used around the surgical field, causing many concerns about their relationship with surgical site infection (SSI). [2][3][4] However, there are still many controversies about the effect of these active warming devices on the rate of SSI after surgery.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
“…4 Although these warming devices are known to be effective in preventing hypothermia, they had to be used around the surgical field, causing many concerns about their relationship with surgical site infection (SSI). [2][3][4] However, there are still many controversies about the effect of these active warming devices on the rate of SSI after surgery. 5,6 In addition, there has been no study on the association in posterior spinal fusion surgery, which is performed in a relatively large number compared to other spinal surgeries but has a higher SSI rate.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
“…Alongside relatively lacking clinical literature relating warming interventions directly against SSI presentation and related patient recovery measures, existing studies have also yielded conflicting conclusions. Most recently in 2015, Ousey et al 15 concluded that while both active and passive perisurgical warming conferred significant benefits toward some reduction in short-term inpatient SSI recordings, follow-up tracking data suggested that these benefits disappeared when evaluated by more longitudinal factors such as SSI-related hospitalisations, further acute exacerbation, or long-term morbidity and mortality of attributable cause. Contemporary research from paediatric spine procedures indicate that surgical warming interventions significantly reduce postoperative bleeding and blood transfusion volume but generally fail to produce meaningful decreases in patient-centred results, including SSI severity and length of admittance.…”
Section: Introductionmentioning
confidence: 99%